A Study on a Quantitative Analysis Method for Fire and Explosion Risk Assessment of Offshore Platforms - Zhaohui Shang; Huibin Yan; Weidong Ruan; Yong Bai (Advances in Civil Engineering)
Proper design of the explosion loads is of vital importance in the risk assessment of explosions for offshore oil and gas installations. A quantitative assessment method for gas explosion loads in process modules of offshore platform is proposed in this paper. The proposed approach achieves the following three objectives: (a) defining a suitable number of leak scenarios quantitatively based on the Latin Hypercube Sampling (LHS) technique and statistical analysis; (b) defining the explosion scenarios according to the computational fluid dynamics (CFD) dispersion analysis results in the sampled leak scenarios; (c) designing the explosion loads on interested areas according to the CFD analysis results in different explosion scenarios and exceedance probability methods. The proposed method was applied to a process module of an example offshore platform. The pressure loads on interested areas of the example platform are very close to that suggested in Det Norske Veritas (DNV) codes. The method developed in this paper can benefit the engineers on better assessment of gas explosion risk in process modules for offshore installations.